The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1038/s41467-018-03099-x
|View full text |Cite
|
Sign up to set email alerts
|

Integrative genomic profiling of large-cell neuroendocrine carcinomas reveals distinct subtypes of high-grade neuroendocrine lung tumors

Abstract: Pulmonary large-cell neuroendocrine carcinomas (LCNECs) have similarities with other lung cancers, but their precise relationship has remained unclear. Here we perform a comprehensive genomic (n = 60) and transcriptomic (n = 69) analysis of 75 LCNECs and identify two molecular subgroups: “type I LCNECs” with bi-allelic TP53 and STK11/KEAP1 alterations (37%), and “type II LCNECs” enriched for bi-allelic inactivation of TP53 and RB1 (42%). Despite sharing genomic alterations with adenocarcinomas and squamous cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

31
343
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 272 publications
(375 citation statements)
references
References 64 publications
31
343
1
Order By: Relevance
“…The value of INSM1 in an algorithm of ≥2 neuroendocrine markers staining for biopsies to recognise LCNEC is unclear. Furthermore, recent studies have addressed the existence of different molecular subtypes of LCNEC . Proposed are the LCNEC‐SCLC with TP53/RB1 mutations recognised with IHC by loss of the RB1 protein and the LCNEC‐NSCLC subtype with STK11/KEAP/KRAS mutations and the presence of RB1 protein staining .…”
Section: Discussionmentioning
confidence: 99%
“…The value of INSM1 in an algorithm of ≥2 neuroendocrine markers staining for biopsies to recognise LCNEC is unclear. Furthermore, recent studies have addressed the existence of different molecular subtypes of LCNEC . Proposed are the LCNEC‐SCLC with TP53/RB1 mutations recognised with IHC by loss of the RB1 protein and the LCNEC‐NSCLC subtype with STK11/KEAP/KRAS mutations and the presence of RB1 protein staining .…”
Section: Discussionmentioning
confidence: 99%
“…Two studies have recently reported the classification of LCNEC into subgroups using next generation sequencing …”
Section: Discussionmentioning
confidence: 99%
“…George et al . classified LCNEC into two subtypes, named type I LCNEC and type II LCNEC, not only based on gene mutational profiles (such as TP53 or RB1 ) but also on neuroendocrine gene expression profiles using the RNA sequencing expression data on 69 LCNECs and 110 SCLCs . These authors found that despite their gene mutational patterns, type I LCNEC lacking of TP53 and RB1 coalteration exhibited high expression of neuroendocrine genes with closest similarity to those of SCLC, and type II LCNEC with coalteration of TP53 and RB1 revealed reduced expression of neuroendocrine genes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations